Neighboring Optimal Control for Mobile Robot Trajectory Tracking with Range-Limited Sensors - Miah, M. Suruz; Gueaieb, Wail; Spinello, Davide; Khan, Kaisar (Université d'Ottawa | University of Ottawa, 2015)
Among the major challenges in tracking a pre-defined trajectory of a nonholonomic mobile robot operating in indoor environments is to determine an appropriate feedback control. In the technical literature, numerous controllers have been proposed to date for solving trajectory tracking and/or regulation problems of mobile robots. Most of them are quite promising to implement and mobile robots can operate in quite complex environments with these controllers. Nevertheless, one of the shortcomings of most of the existing controllers is the requirement of sophisticated hardware, which, in some cases, more costly than the mobile robot itself. In addition, the analytical expression for most of the controllers is quite complex even for a simple nonholonomic system, an unicycle, for example. In this paper, we propose a neighboring optimal controller coupled with the state estimation for a differential drive mobile robot to track a pre-defined trajectory using signal strength measurements from RF (radio frequency) sensors placed in its operating environment. We emphasize that the RF sensors have limited communication range with the robot. The proposed controller is easy to implement, does not require sophisticated hardware for processing, and has relatively easier expression for the feedback controller. A numerical example is provided to validate the theoretical results. Computer simulations will be backed by experimental results for future investigations.
Keywords: Optimal control; Mobile robotics; Robot localization; Trajectory tracking